Effect of annealing temperature and dopant concertration on the surface layer of indium doped Ba0.5Sr0.5Ti03 thin film - Noor Khairul Anuar Johari
The purpose of this project is to fabricate barium strontium titanate (BST) and Indium doped barium strontium titanate (BIST) thin films using the chemical solution deposition (CSD) method with 1.00 M precursor.